Gestational weight loss and perinatal outcomes in overweight and obese women subsequent to diagnosis of gestational diabetes mellitus - Yee, Lynn M. (2013)
OBJECTIVE: To investigate whether gestational weight loss after the diagnosis of gestational diabetes mellitus (GDM) in overweight and obese women is associated with improved perinatal outcomes. Obesity and GDM are risk factors for adverse perinatal outcomes, but few studies have investigated weight loss during pregnancy in women with these comorbidities. METHODS: Retrospective cohort study of 26,205 overweight and obese gestational diabetic women enrolled in the California Diabetes and Pregnancy Program. Women with gestational weight loss (GWL) during program enrollment were compared to those with weight gain. Perinatal outcomes were assessed using chi-square test and multivariable logistic regression analysis. RESULTS: 5.2% of women experienced GWL. GWL was associated with decreased odds of macrosomia (aOR 0.63, 95% CI 0.52–0.77), NICU admission (aOR 0.51, 95% CI 0.27–0.95), and cesarean delivery (aOR 0.81, 95% CI 0.68–0.97). Odds of SGA status (aOR 1.69, 95% CI 1.32–2.17) and preterm delivery <34 weeks (aOR 1.71, 95% CI 1.23–2.37) were increased. CONCLUSIONS: In overweight and obese women with GDM, third trimester weight loss is associated with some improved maternal and neonatal outcomes, although this effect is lessened by increased odds of SGA status and preterm delivery. We recommend further research on weight loss and interventions to improve adherence to weight guidelines in this population.